Spatial distribution of Phlebotominae in Puerto Iguazú-Misiones, Argentina-Brazil- Paraguay border area - Santini, Maria Soledad (2013)
The first Argentinian autochthonous human case of visceral leishmaniasis (VL) was confirmed in Posadas (Misiones) in 2006. Since then, the disease has increased its incidence and geographical distribution. In the 2006-2012 period, 107 human cases were detected (11 deaths). The presence of Lutzomyia longipalpis was detected in peridomiciles in Puerto Iguazú urban area in 2010; some of these findings were associated with households where cases of canine VL had already been reported. The objective of this study was to ascertain the abundance and spatial distribution of Lu. longipalpis in Puerto Iguazú City, on the Argentina-Brazil-Paraguay border. Lu. longipalpis proved to be exclusively urban and was found in 31% of the households sampled (n = 53), 67% of which belonged to areas of low abundance, 20% to areas of moderate abundance and 13% to areas of high abundance. Nyssomyia whitmani was the only species found both in urban and peri-urban environments, and Migonemyia migonei was registered only on the outskirts of the city. Due to the fact that Puerto Iguazú is considered to be at moderate risk at the moment, it is necessary to intensify human and canine case controls, as well as take integrated prevention and control measures regarding the environment, vectors and reservoirs on the Argentina-Brazil-Paraguay border area.